New Iteration Methods for Time-Fractional Modified Nonlinear Kawahara Equation - Abdon Atangana; Necdet Bildik; S. C. Oukouomi Noutchie (Abstract and Applied Analysis)
We put side by side the methodology of two comparatively new analytical techniques to get to the bottom of the system of nonlinear fractional modified Kawahara equation. The technique is described and exemplified with a numerical example. The dependability of both methods and the lessening in computations give these methods a wider applicability. In addition, the computations implicated are very simple and undemanding.